(untitled) (Research, Society and Development, 2021)
Objective: To analyze the perception of students about the applicability of the Systematization of Nursing Care (SAE) in the realistic simulation scenario and how this process contributes to academic learning. Method: Integrative literature review on the use of realistic simulation as a tool for learning the systematization of nursing care. For greater methodological assertiveness, the following PICO question was used: Does training in the Systematization of Nursing Care through realistic simulation bring better results in the learning of nursing students compared to traditional teaching methods? The bibliographic data of the study were collected electronically, through the VHL, the descriptors used were: “Training by simulation” and “Nursing students”, with Boolean operations “AND”. Results: Eight studies were analyzed, namely: cross-sectional, quasi-experimental, randomized experimental and intervention research, in the interval between 2016 and 2021, in English and Portuguese. randomized from 2016 to 2021, in English and Portuguese. In all articles verified, realistic simulation is seen as an important teaching method for the development of Nursing Care Systematization. Conclusion: The study could conclude that students, after the scenarios, were aware of their mistakes before receiving feedback from their preceptors. Therefore, realistic simulation can be a good alternative to facilitate safety, avoid errors and solidify the learning of nursing care systematization.